Hewlett-Packard Company : the departure of Mark Hurd (A) - Martin, Kevin (SAGE Knowledge. Cases., 2017)
For five years Mark Hurd has enjoyed dramatic success as the CEO of Hewlett Packard, turning the companys PC division around and getting the company back in the black through aggressive cost-cutting, including the elimination of 14,500 jobs. However, employee morale is through the floor and there may be high turnover costs down the road. When Hurd is accused of sexual harassment by a female contractor, and her attorney is the high-profile feminist Gloria Allred, H-Ps Board of Directors has a very difficult decision to make. Should the board use the sexual harassment accusation as an excuse to oust the wildly successful but unpopular CEO?